(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The coir fibre currently recognized as one of the sustainable fibre composite material, due to some specific mechanical property when compared to artificial fibre. Also, when compared to plain cement concrete, the coir reinforced concrete improves the cracking resistance. Addition of coconut fibre in concrete improves various engineering properties of concrete, because it possesses good binding property in concrete. In this experimental study different dimension of coir fibre is randomly distributed into concrete of M25 grade with water-cement ratio of 0.43. The coir fibre with a length of 10mm, 15mm and 20mm of different percentage as 0.1%, 0.15%, 0.20%, 0.25%, and 0.30% are used respectively. Due to the presence of coir fibre there is a decrease in the workability of concrete. The test on compressive strength for 28 days is carried out for all the selected proportions of coir fibre. And the maximum compressive strength was obtained for a mix having a fibre length of 15 mm and 0.2% of coir fibre content. Based on the experimental study it is noticed that the compressive strength found to be decreases with increasing length and percentage of coir fibre. So, in the field of civil engineering, more importance and encouragement should be given for the use of natural fibres which are locally available materials..